Diversity of Insect Types on Rice (Oryza Sativa L.) Crops in Minahasa District - Lengkong, Maxi; Wanta, Noni N.; Paruntu, Masye B. (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
The aim of the research is to determine the types and diversity of insects on rice plants in West Kakas District, Minahasa Regency. It is hoped that this research can provide information on the presence of insects that live and are associated with lowland rice plants so that insect pest control strategies can be implemented that are right on target, on time and for their proper use. The research will be carried out based on the purposive sampling method aimed at 5 observation points carried out at 4 locations and the method of catching insects is carried out directly and using insect nets. Research results show that insects are pests and natural enemies. Pest insects consist of 5 orders, 12 families and 16 species, namely Dolycorus sp, Scotinophara sp. , Stenodema sp, Leptocorisa sp, Paraecosmetus sp, Cofana spectra, Recilia sp ., Nephotetix sp, Oxya sp. , Anacridium sp, Chilo sp, Parnara sp, Cnaphalocrocis sp . , Orseolia sp , Chlorops sp , and Phyllotretra sp. Meanwhile, natural enemies consist of 3 orders, 9 families and 9 species, namely Cyrtohinus sp . , sp, Agryophylax sp . , Sepedon sp., Encarsia sp., Menochilus sp. , Ophionea sp . , Paederus sp., Sceliphron sp. and Agriocnemis sp. The results of Shannon and Wiever's diversity analysis are H' = 2.81 or moderate diversity index , richness index R = 4.67 or medium criteria value, evenness index E = 0.52 or moderate and unstable evenness index, and dominance index C = 0.37 or low dominance.